Penelitian pengaruh pemakaian penguat kain flanel dan penguat kain kaos terhadap uji fisis kulit imitasi untuk atasan sepatu - Suprapto Suprapto (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1998)
The aim of this research is to find out the influence on the woven fabric of synthetic leather to the quality of the sport shoes conducted by physical test. This research compare the flannel material with cotton and polyester material. Tresult of the physical test of the tensile strength elongation at break, peel resistances value both vertically or horizontally showed that synthetic leather flannel of the sport shoes significantly different with the cotton and polyester synthetic leather of the sport shoes. However for tearing resistance whether vertically or horizontally, flannel material syntactic leather and cotton polyester synthetic leather for the sport shoes are not significantly different. INTISARI Penelitian ini bertujuan untuk mengetahui pengaruh bahan penguat kulit imitasi untuk atasan sepatu ditinjau dari uji fisis. Penelitian ini memvariasikan jenis bahan penguat untuk bahan kulit imitasi, yaitu bahan kain flannel dan bahan kain kaos. Dari hasil pengujian sifat fisis menunjukkan bahwa: tegangan putus, perpanjangan putus, ketahanan rekat baik arah melintang maupun arah membujur bahan penguat kain flanel kulit imitasi untuk atasan sepatu dengan bahan penguat kain kaos kulit imitasi untuk atasan sepatu perbedaan tidak nyata.